Topical Anti-TNFα Agent Licaminlimab (OCS-02) Relieves Persistent Ocular Discomfort in Severe Dry Eye Disease: A Randomized Phase II Study - Shettle, Lee; McLaurin, Eugene; Martel, Joseph; Seaman, John W; Weissgerber, Georges (Clinical ophthalmology (Auckland, N.Z.), 2022)
Purpose: To assess the efficacy, safety, and pharmacokinetics of new topical ocular anti-TNFα antibody fragment licaminlimab in the relief of persistent ocular discomfort in severe dry eye disease (DED). Patients and Methods: Patients with ≥ 6-month history of DED, regular use of artificial tears, and best-corrected visual acuity (BCVA) of ≥ 55 letters in each eye (Early Treatment Diabetic Retinopathy Score) at baseline were included in this multicenter, randomized, vehicle-controlled, double masked study. A total of 514 patients were screened. After a 2-week run-in with Vehicle, all qualifying patients received Vehicle eye drops for 4 weeks. Patients with global ocular discomfort score ≥ 50 at the end of this 4-week period were randomized to receive licaminlimab (60 mg/mL ophthalmic solution) (69 patients) or Vehicle (65 patients) for 6 weeks. The primary efficacy endpoint was change from baseline in global ocular discomfort score at Day 29. Safety assessments included adverse events and ophthalmology examination including intraocular pressure (IOP). Serum licaminlimab levels were also determined. Results: Change from baseline to Day 29 in global ocular discomfort score was statistically significantly greater for licaminlimab than for Vehicle (p = 0.041). No safety issues were identified. Serum licaminlimab was undetectable in most patients; the maximum concentration observed was 8.47 ng/mL. Conclusion: Topical ocular licaminlimab demonstrated statistically significant improvement in global ocular discomfort score compared to Vehicle in patients with severe DED, with good tolerability, no increase in IOP, and minimal systemic drug exposure.